2014
DOI: 10.3136/fstr.20.715
|View full text |Cite
|
Sign up to set email alerts
|

Response Surface Optimization of Extraction and Antioxidant Activity of Total Flavonoids from Seed Shell of Juglans mandshurica

Abstract: The seed shell of Juglans mandshurica is a waste product from seed kernel processing in the food industry. For

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…With respect to C. ovata seeds, some researchers have only reported that fatty acids in seed oil have an inhibitory effect on rodent colon cancer [23]. At present, the correlation study between antioxidant activities and the content of total flavonoids involving in sea buckthorn [24], pomegranate [25], Zanthoxylum bungeanum [26], Juglans mandshurica [27], Peanut [28], Garcinia kola Seeds [29], Rhynchosia volubilis [30], Oroxylum indicum [31], and Colored Chickpea [32] had been carried out. However, the phytosterols and tocopherols in C. ovata seed oil and the flavonoids in defatted seed meal as well as related activities were not reported.…”
Section: Introductionmentioning
confidence: 96%
“…With respect to C. ovata seeds, some researchers have only reported that fatty acids in seed oil have an inhibitory effect on rodent colon cancer [23]. At present, the correlation study between antioxidant activities and the content of total flavonoids involving in sea buckthorn [24], pomegranate [25], Zanthoxylum bungeanum [26], Juglans mandshurica [27], Peanut [28], Garcinia kola Seeds [29], Rhynchosia volubilis [30], Oroxylum indicum [31], and Colored Chickpea [32] had been carried out. However, the phytosterols and tocopherols in C. ovata seed oil and the flavonoids in defatted seed meal as well as related activities were not reported.…”
Section: Introductionmentioning
confidence: 96%
“…Ethanol aqueous was selected as the extraction solvent in this study because of its safety, easy accessibility and high affinity for antioxidants compared with other organic solvents [27,28,29]. Different ethanol concentrations had different polarities.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the high solvent costs, the toxicity resulting from the solubility of the bioactive compounds in the solvent and low extraction efficiency, these solvents have been used regularly for the extraction of antioxidant compounds. Therefore, ethanol is one of the appropriate extraction solvents for antioxidant compounds due to its low cost, "green" characteristics, ease of access and safety for direct use in foods and pharmaceuticals (Xu & Bao 2014, Dailey & Vuong 2015.…”
Section: Introductionmentioning
confidence: 99%